VA-Wide, Multicenter Verification Study of the Cepheid Xpert SARS-CoV-2 Assay - Mohammad Obeidat MBBS; Amy R. Frank MT (ASCP); Michael S. Icardi MD; J. Stacey Klutts MD, PhD (Elsevier, 2021)
Early in the Severe Acute Respiratory Syndrome Coronavirus 2 pandemic, there was a progressive increase in diagnostic demands that developed within a relatively short period of time. On February 4, 2020, the Secretary of Health and Human Services issued the Emergency Use Authorization for in vitro diagnostics assays for the Severe Acute Respiratory Syndrome Coronavirus 2 virus. Subsequently, multiple assays were approved under the Emergency Use Authorization, including the Cepheid Xpert SARS-CoV-2 assay. Presented here is a description of the nationally coordinated verification study of the Cepheid assay that was performed within the Veteran's Affairs Health System. This coordinated study helped to expedite the verification process for a majority of the Veteran's Affairs system labs, preserved precious system resources, and highlighted the power of a national medical system in response to an emergency.